Supramolecular assemblies and magnetic behaviors of the M(II)/p-aminopyridine/malonate (M = Ni, Mn, Cu, Co) systems - Fernandes, Ronaldo J. [UNESP]; Frem, Regina C. G. [UNESP]; Da Silva, Patrícia B. [UNESP]; Freitas, Rafael S.; Silva, Patrícia; Fernandes, José A.; Rocha, João; Almeida Paz, Filipe A. (Elsevier, 2013)
The coordination compounds [Ni(μ-mal)(apy)2(H 2O)]·2.8H2O (1), [Mn(μ-mal)(H2O) 2] (2), (apyH)2[Cu(μ-mal)2] (3) and (apyH)2[Co(mal)2(H2O)2] (4) (mal = malonate, apy = p-aminopyridine) have been synthesized and characterized by elemental analysis, vibrational spectroscopy, single crystal X-ray diffraction and magnetometry. With exception of 4, the malonate group acts as bridging ligand leading to the formation of one-dimensional polymeric chains. In compound 1 it was observed the coordination of the p-aminopyridine in the axial positions of the distorted octahedral coordination sphere. The solid-state structure exhibits a high complex 3D network formed by several supramolecular interactions. Magnetic properties were determined for all members of the series and indicate that the materials behave are normal paramagnets, except the Mn polymer 2 which exhibits an antiferromagnetic ground state. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Coordination solids; Crystal structures; Magnetic properties; Malonate p-Aminopyridine; Nickel